Collaborative Governance and Management in Forest and Critical Land Rehabilitation: A West Java Case Study - Elvan Robiyana; Tati Sarihati (Journal of Educational Management Research, 2025)
Protected forest management in Indonesia, particularly in Sukabumi Regency, faces various challenges related to policy implementation and inter-agency coordination. This study aims to analyze protected forest management in Sukabumi through the application of good governance principles, with a focus on improving institutional capacity and coordination between stakeholders. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, documentation studies, and field observations. The results indicate that the main obstacles in protected forest management are budget constraints, low inter-agency coordination, and the community's economic dependence on forest resources. Although planning is in place, implementation in the field remains limited. This study concludes that strengthening technical capacity, inter-agency coordination, and more consistent application of good governance principles can increase the effectiveness of protected forest management. The contribution of this research is to provide practical solutions to improve forest governance and enhance the sustainability of protected forest management in Indonesia.